2015
DOI: 10.3109/02813432.2015.1001943
|View full text |Cite
|
Sign up to set email alerts
|

GPs’ negotiation strategies regarding sick leave for subjective health complaints

Abstract: Objectives. To explore general practitioners’ (GPs’) specific negotiation strategies regarding sick-leave issues with patients suffering from subjective health complaints. Design. Focus-group study. Setting. Nine focus-group interviews in three cities in different regions of Norway. Participants. 48 GPs (31 men, 17 women; age 32–65), participating in a course dealing with diagnostic practice and assessment of sickness certificates related to patients with subjective health complaints. Results. The GPs identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…This is in accordance with previous findings. [ 40 ] A lack of an objective measure of nausea to enable documentation for NAV on the grounds on which the sick leave is being prescribed was mentioned in relation to the sick leave dilemma. The Pregnancy-Unique Quantification of Emesis (PUQE) scale has been translated into Norwegian and is included in the new national guideline for treatment of NVP.…”
Section: Discussionmentioning
confidence: 99%
“…This is in accordance with previous findings. [ 40 ] A lack of an objective measure of nausea to enable documentation for NAV on the grounds on which the sick leave is being prescribed was mentioned in relation to the sick leave dilemma. The Pregnancy-Unique Quantification of Emesis (PUQE) scale has been translated into Norwegian and is included in the new national guideline for treatment of NVP.…”
Section: Discussionmentioning
confidence: 99%
“…Other questions also arise with respect to the strategies that should be implemented simultaneously to preserve a working alliance with the patient. Studies such as those by Money et al [ 31 ] and Nilsen et al [ 32 ] have provided good descriptions of the potential for conflict during the negotiation of sick leave and RTW. It is likely that a proactive approach towards work, as described by profile 1, may generate such conflicts.…”
Section: Discussionmentioning
confidence: 99%
“…In the medical profession, however, this role conflict is widely acknowledged (Alexanderson et al, 2009;Angell, 1993;Arnesen & Fredriksen, 1995;Ayres, 1996;Carlsen & Norheim, 2005;Pearson, 2000). Several empirical studies have found that primary care physicians are indeed reluctant to reject patients' requests for sickness certificates (Carlsen & Norheim, 2003;Englund, Tibblin, & Svärdsudd, 2000;Gulbrandsen, Førde, & Aasland, 2002;Larsen, Førde, & Tellnes, 1994;Nilsen, Malterud, Werner, Maeland, & Magnussen, 2015;Wahlström & Alexanderson, 2004).…”
Section: Introductionmentioning
confidence: 99%